USE OF THE RAMP METERING SYSTEM AT TWO-LEVEL JUNCTIONS - A. N. Novikov; I. A. Novikov; A. G. Shevtsova; A. G. Burlutskaya (Вестник СибАДИ, 2019)
Introduction. The paper describes the method of increasing the capacity of transport interchanges, providing entry into the city, on the example of Belgorod and through the introduction of traffic light control system - Ramp metering. The authors investigate 4 transport interchanges at the entrances to the regional center and evaluate geometric parameters of the congresses. Moreover, the authors select the optimal site for the implementation of the Ramp measuring system, basing on the analysis of geometric parameters and calculations of intensity parameters and time delays.Methods and materials. The use of intelligent transport systems in cities and urban agglomerations traffic management allows minimizing vehicles delays and such method is quite topical for traffic organization at peak times and reduction of accidents through the use of intelligent machine control of the vehicle flows.Results. The authors develop the approach to the intelligent transport systems’ usage at the entrance areas to the cities and urban agglomerations, which takes into account changes in the basic parameters of traffic flow and geometric parameters of transport interchanges.Conclusion. As a result, it is necessary to use intelligent transport systems through the introduction of Ramp measuring system, as well as through the study of changes in the basic parameters of traffic flow and geometric characteristics of urban transport interchanges.